2019
DOI: 10.1038/s41398-019-0523-5
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent stress across life may improve cognitive performance in individual rats, suggesting the induction of resilience

Abstract: Depressive symptoms are often accompanied by cognitive impairments and recurrent depressive episodes are discussed as a potential risk for dementia. Especially, stressful life events are considered a potent risk factor for depression. Here, we induced recurrent stress-induced depressive episodes over the life span of rats, followed by cognitive assessment in the symptom-free period. Rats exposed to stress-induced depressive episodes learned faster than control rats. A high degree of stress-induced depressive-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…One potential explanation is that more significant life disruptions with diagnosis increased motivation and effort for attentional control as an adaptive coping mechanism; studies such as Fields et al (2021) mentioned that exposure to early caregiving instability can lead to both decrements and enhancements in cognitive control, with potential for adaptation. Also, Moser et al (2012) showed that trait anxiety is associated with increased attentional distraction, suggesting a general enhancement of bottom-up processes involved in motivational significance detection; Hadar et al (2019) mentioned that Recurrent stress may also have a beneficial effect on cognitive performance in some individuals, potentially inducing resilience.…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation is that more significant life disruptions with diagnosis increased motivation and effort for attentional control as an adaptive coping mechanism; studies such as Fields et al (2021) mentioned that exposure to early caregiving instability can lead to both decrements and enhancements in cognitive control, with potential for adaptation. Also, Moser et al (2012) showed that trait anxiety is associated with increased attentional distraction, suggesting a general enhancement of bottom-up processes involved in motivational significance detection; Hadar et al (2019) mentioned that Recurrent stress may also have a beneficial effect on cognitive performance in some individuals, potentially inducing resilience.…”
Section: Discussionmentioning
confidence: 99%
“…As a confirmatory test, these miRNAs, when injected in vitro into the zygote, showed a decreased cortisol level (41). There are other studies stating that experiences and stresses in life improve cognitive function and provide resilience (43); however, the exact mechanism of transgenerational/intergenerational inheritance remains unknown. Several early stressors and experiences in life have been shown to improve tolerability in the future.…”
Section: Sperm Sncrnas In Transgenerational Inheritancementioning
confidence: 93%
“…However, it is known that memory retention is enhanced after stress ( Roozendaal and McGaugh, 1996 ; Barsegyan et al, 2010 ), whereas memory retrieval is impaired under stress ( De Quervain et al, 1998 ; Cai et al, 2006 ). Interestingly, recurrent stress across life has been shown to improve cognitive performance in individual rats ( Hadar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%